(untitled) (Editora Impacto Científico, 2025)
The Family Health Strategy (FHS) is based on the work of interdisciplinary teams to ensure the comprehensiveness and problem-solving capacity of Primary Health Care (PHC). However, the implementation of this collaboration faces multiple challenges. This study aims to identify and analyze the main obstacles to interdisciplinary work in family health teams, based on a literature review. The analysis reveals that the central challenges include: systemic pressures, such as work overload and shortage of professionals, which fragment care; gaps in training and continuing education, which do not adequately prepare for collaborative competencies; lack of definition of roles and clinical leadership models within teams; and the complexity of expanding collaboration to achieve effective intersectoral coordination with the community and other social resources. It is concluded that overcoming these challenges is imperative for strengthening PHC. This requires strategic investments in continuing education, clear definition of responsibilities, and the creation of policies that encourage and structure collaborative practices, aiming to improve the quality of care and promote health equity. DOI: https://doi.org/10.56238/edimpacto2025.090-005